Bovine Polyclonal Anti-eCG and eCG Combinated Vaginal Sponges Progesterone to Induce Estrus and Pregnancy of Etawa Crossbred Goats - Herry Agoes Hermadi1 , Sunaryo Hadi Warsito2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Equine chorionic gonadotropin (eCG) like folligon is a gonadotropin hormon derived from blood sera inpregnant mare 30 till 140 days. The repeated use of eCG treatments for the induction of ovulation is generallyfollowed can decrease in fertility. Bovine anti-eCG antibodies (Abs) as research result in UniversitasAirlangga in 2019 can solve the problem of decrease in fertility in does. The objective of this study was toevaluate the reproductive performance of subjected to a short-term protocol for estrus induction using 50mg of vaginal sponges’ progesterone. The experimental animal used in this study comprised of 30 etawaCrossbred goats, with normal estrus cycle and 3 years old of age. The etawa crossbred goat are all healthywith a body score of at least three. 30 goats divided become 3 groups Group I as (T0) 10 goats are as controlsGroups. (T0) was inserted sponge progesterone 50 mg of MPA and injected with PGF2? 7.5 mg in day 10intramuscular (im) when T0 removal of the sponge were removed on day 11. Does on day 11 as T1 going onthe removal of devices 24 h before removal inject 7.5 mg of PGF2? and 300 IU of eCG. T2 were injected inall the goats 7.5 mg of PGF2?, 300 IU of eCG at day 10 and 300 IU bovine anti eCG inject at day 11 whenremoval device on day 11. After 35 days, pregnancy was diagnosed by ultrasound scanning. Short-termprotocols using either an intravaginal device was similarly effective to estrus induction 100% p >0.05, andall goats from both groups had estrus manifestation within 30 h after device removal, duration of estrus 37h and doing AI. In addition, no significant difference in pregnancy p >0.05 on 35 days.